CONSUMER EXPERIENCE AS A FACTOR OF STUDENT LOYALTY IN HIGHER EDUCATION - Sotikova, Natalija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Intensive competition in contemporary education market makes higher educational institutions choose market focused strategy in order to make their offer outstand their other competitors. Defining the factors of experience development, their impact on satisfaction and loyalty of foreign students would help higher educational institutions to create positive experience for foreign students that would later, thanks to this experience, can become loyal and spread positive information about the higher educational institution. Research of these factors is especially topical for Latvia because one of the main directions for development of the state educational system is integration in international educational system. The objective of research is to study the impact of experience developing factors on forming satisfaction and loyalty in higher education. Survey has been used as a research method, questionnaire covered foreign students in Latvia. Data analysis has been conducted with frequency analysis, calculations of central tendency indicators, correlation analysis and path analysis. As a result, it was found that satisfaction with higher educational institution was mainly formed with its capability to fulfil its obvious functions, that is provide qualitative education corresponding with expectations of foreign students. The analysis of impact of general satisfaction with higher educational institution on loyalty demonstrated very strong positive influence: the higher the satisfaction, the more likely foreign students would consider studies in particular higher educational institution to be useful for other foreign students and advise it.